Exploration of Intergenerational Interaction in the Context of Contemporary Families: A Review from a Sociological Perspective - Manurung, Lengsi (International Humanity Advance, Business & Sciences, 2025)
This study explores intergenerational interaction in the context of contemporary families from a sociological perspective. The main focus of this research is how value shifts and social changes influence relationships between older and younger generations within families. The findings reveal tension between older generations, who preserve traditional values, and younger generations, who are more open to change. However, there are also opportunities for mutual learning, both in terms of technology and cultural values. Changes in family structure, particularly the shift toward nuclear families, and the adoption of technology, play a significant role in shaping communication between generations. The study concludes that, despite challenges in intergenerational interactions, open dialogue and mutual learning can strengthen relationships within contemporary families.